Pengaruh Produk Domestik Regional Bruto (PDRB), Dana Alokasi Umum, dan Pendapatan Asli Daerah (PAD) terhadap Alokasi Belanja Daerah di Kabupaten/Kota Provinsi Jawa Tengah (Studi Kasus Tahun 2013-2017) - Fauzan Arioyuda; Nugroho SBM (Universitas Diponegoro, 2020)
The implementation of local autonomy and fiscal decentralization in Indonesia is an strategic step to increase the local independence in the financial and strengthen the local economy base. Although the local has been given great authority to manage potential sources of local revenue, the fact the level of local independence in the financial sector have not shown significant progress. The local government is still dependent on the central government to support development activities and public services for the community at the local level. This research aims to prove empirically the influence of gross regional domestic product, balance funds, and regionally original income to local government expenditure in regencies and cities at Central Java Province. The data that used in this research are quantitave data with the type of panel data in the form of an annual. Time series data started from the period 2013 to 2017, while its cross section data are 35 regencies and cites in Central Java Province. From the merger of two kinds of data has yielded 170 observations. The analysis method that used is panel data regression with fixed effects model approach.